(untitled) (Research, Society and Development, 2021)
This study aimed to analyze the adherence of teachers, students and other education professionals regarding the implementation and progress of remote education during the COVID-19 pandemic in the context of higher education. This is an exploratory research of a quantitative nature, carried out in the municipality of Mossoró, State of Rio Grande do Norte. The study population consisted of teachers, students and education professionals at the level of coordination or supervision. For that, a questionnaire was applied electronically through the Google forms tool. The data obtained were tabulated with the aid of electronic spreadsheets and arranged for presentation of results through statistical graphics and percentages. Due to a low percentage of absences, good connectivity and handling of basic services to maintain the stability of activities in remote classes, it is possible to fulfill that students and teachers, as well as other higher education professionals from Mossoró - RN student adherence to the distance learning method. However, it was found that despite accepting this teaching method as a temporary solution to the pandemic period, 67% of respondents reported that their learning was impaired, while 19% said they remained the same, and only 14% of respondents said it improved.